Implementation of Public Information Transmission in the Province of East Kalimantan - Muhamad Yusuf (Universitas Syiah Kuala, 2023)
One form of effort to improve public information transparency services, is by making innovation changes that are carried out in accordance with Permendagri Number 3 of 2017. This research raises the issue of implementing the Public Information Disclosure policy in the East Kalimantan Provincial Government. This study uses a post positivist approach with qualitative methods. The results of this study indicate that (i) the implementation of the public information disclosure policy in East Kalimantan Province has been running effectively as evidenced in 2021 the East Kalimantan Government received an Informative Province award; (ii) to encourage the implementation of the public information disclosure policy in East Kalimantan Province, the recommended action is to increase the knowledge and understanding of the Information and Documentation Management Officer (PPID). Continuously it is necessary to carry out a Technical Guidance or Communication Forum to be able to provide explanations and discuss together with the Regional Apparatus Implementing PPID regarding the duties, principals and functions of the PPID, as well as a mechanism for managing public information exceptions as well as a mechanism for handling public information objections and disputes